Oxidative and antioxidative status of children with acute bronchiolitis - Rusen Dundaroz; Ufuk Erenberk; Ozden Turel; Aysegul Dogan Demir; Emin Ozkaya; Ozcan Erel (Jornal de Pediatria (Versão em Português), 2013)
Objective: Oxidative stress has been shown to contribute to the pathogenesis of acute and chronic lung inflammatory diseases. This article aimed to evaluate the oxidant/antioxidant status of children with acute bronchiolitis through the measurement of plasma total antioxidant capacity, total oxidant status, and oxidative stress index. Methods: Children with acute bronchiolitis admitted to the pediatric emergency department of a university hospital between January and April of 2012 were compared with agematched healthy controls. Patients with acute bronchiolitis were classified as mild and moderate bronchiolitis. Oxidative and antioxidative status were assessed by measurement of plasma total antioxidant capacity, total oxidant status, and oxidative stress index. Results: Thirty-one children with acute bronchiolitis aged between 3 months and 2 years, and 39 healthy children were included. Total oxidative status (TOS) was higher in patients with acute bronchiolitis than the control group (5.16±1.99 μmol H2O2 versus 3.78±1.78 μmol H2O2 [p = 0.004]). Total antioxidant capacity (TAC) was lower in children with bronchiolitis than the control group (2.51±0.37 μmol Trolox eqv/L versus 2.75±0.39 μmol Trolox eqv/L [p = 0.013]). Patients with moderate bronchiolitis presented higher TOS levels than those with mild bronchiolitis and the control group (p = 0.03, p < 0.001, respectively). Patients with moderate bronchiolitis had higher oxidative stress index levels than the control group (p = 0.015). Oxygen saturation level of bronchiolitis patients was inversely correlated with TOS (r = –0.476, p < 0.05). Conclusion: The balance between oxidant and antioxidant systems is disrupted in children with moderate bronchiolitis, which indicates that this stress factor may have a role in the pathogenesis of the disease.